Stated market preferences of dairy producers in the presence of a dairy cooperative: Insights from an exploratory visit to the rural-urban interface of Bengaluru, India - Yashree Mehta (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2024)
An exploratory visit to the rural-urban interface of Bengaluru city revealed that dairy producers with larger herd size and potentially stable income preferred to sell to the cooperative whereas those producers with minuscule herd size (upto two cattle) stated a preference to sell to urban customers in the private market. Sales in the private market were uncertain due to volatile demand but they fetched a higher price than the cooperative per transaction. Given that producers in the latter category were highly cash strapped and needed cash for fulfilling their transaction demand, the stated preferences can be attributed to liquidity concerns on part of the producers. This sets a hypothesis for quantitative research on income stability as a determinant of market choice by dairy producers. This paper provides the linkages between such observed market preferences and the understanding of the producers' and consumers' resilience in terms of food security as well as an understanding of the ethical principles of social embeddedness and moral economy in the context of the production system.
Keywords: 330; Dairy farming; Direct sales; Agricultural cooperative; Revealed preferences; India; Milchviehhaltung; Direktvertrieb; Agrargenossenschaft; Offenbarte Präferenzen; Indien